2019
DOI: 10.5430/rwe.v10n3p273
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy Dynamics of Rural Household Income Diversification: A Review of the International Literature

Abstract: This paper presents a summary of the international literature published on the thematic area of the political economy analysis of income diversification related to the activities of rural households with emphasis on the importance of these activities in economic growth, poverty reduction and sustainable development over time. The review provides information about the overall effect of income diversification on economic welfare of rural householders. Typically, a positive relationship exists between income dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…As noted above, several studies have shown the different benefits of income diversification. Farm households diversify their income to address food insecurity and poverty, stabilize income, and reduce and manage agricultural risks (Awotide et al, 2012; Wan et al, 2016; Atuoye et al, 2019; Etea et al, 2019; Kidane & Zegeye, 2019; Salifu, 2019; Kassegn & Endris, 2021), and invest in innovations and sustain agriculture (Barbieri & Mahoney, 2009; Asravor, 2017). A considerable share (33%–45%, and 27%) of income has been generated from non‐ and off‐farm income sources in sub‐Saharan Africa and Ethiopia, (Devis et al, 2017; Adem et al, 2018), respectively.…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted above, several studies have shown the different benefits of income diversification. Farm households diversify their income to address food insecurity and poverty, stabilize income, and reduce and manage agricultural risks (Awotide et al, 2012; Wan et al, 2016; Atuoye et al, 2019; Etea et al, 2019; Kidane & Zegeye, 2019; Salifu, 2019; Kassegn & Endris, 2021), and invest in innovations and sustain agriculture (Barbieri & Mahoney, 2009; Asravor, 2017). A considerable share (33%–45%, and 27%) of income has been generated from non‐ and off‐farm income sources in sub‐Saharan Africa and Ethiopia, (Devis et al, 2017; Adem et al, 2018), respectively.…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 99%
“…Most literature showed that household income diversification behavior emanated from push (survival‐led) motives such as population growth, declining farm size, rising landlessness, land degradation, low agricultural productivity, insufficient food from conventional farming, poor resource endowment, market failure, seasonality, and risk of environmental shocks (Asfaw et al, 2018; Dagunga et al, 2018; Etea et al, 2019; Loison, 2015). These motives are mainly to address food insecurity and poverty, self‐insurance (manage risks) and sustain agriculture (Dagunga et al, 2018; Etea et al, 2019; Salifu, 2019).…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Theory posits that income diversification activities can be driven by two motives: (a) demand-pull or accumulation-based income diversification and (b) distress-push or security-based income diversification (Dedehouann & Mcpeak 2019; Salifu, 2019). Income diversification based on accumulative motive involves activities with the intention to enhance the extent of capital owned by rural households whose objective would be to establish a minimum threshold of capital needed to maintain their lifestyle and well-being (Dev et al, 2017; Salifu, 2019). Strategies usually adopted for this kind of income diversification include off-agriculture wage-based jobs, migration and land acquisition (Imai et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While family-based economic activities provide opportunities for further economic development, questions have been raised about increasing income inequality among households. Notably, poor rural households find it especially difficult to rise out of poverty because of their limited capabilities to expand income from diversified activities (Salifu, 2019). Scoones (1998) argued that the ability to pursue different livelihood strategies depends on the primary material and social, tangible, and intangible assets that people own.…”
Section: Introductionmentioning
confidence: 99%